2020
DOI: 10.3390/jpm10040267
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Association of Single Nucleotide Polymorphisms with Blood Pressure Response to Hydrochlorothiazide among South African Adults with Hypertension

Abstract: This study described single nucleotide polymorphisms (SNPs) in hydrochlorothiazide-associated genes and further assessed their correlation with blood pressure control among South African adults living with hypertension. A total of 291 participants belonging to the Nguni tribes of South Africa on treatment for hypertension were recruited. Nineteen SNPs in hydrochlorothiazide pharmacogenes were selected and genotyped using MassArray. Uncontrolled hypertension was defined as blood pressure ≥140/90 mmHg. The assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In a study by Turner et al [ 102 ], ADBR2 rs2400707G>A was reported to cause a significant reduction in ambulatory SBP, but not DBP, among the study participants who included Africans. The same SNP was also studied by Masilela et al among South African Nguni tribes [ 103 ]. In this study, they show that A-allele carriers exhibited better BP control and were less likely to develop uncontrolled hypertension.…”
Section: Literature Reviewmentioning
confidence: 82%
See 2 more Smart Citations
“…In a study by Turner et al [ 102 ], ADBR2 rs2400707G>A was reported to cause a significant reduction in ambulatory SBP, but not DBP, among the study participants who included Africans. The same SNP was also studied by Masilela et al among South African Nguni tribes [ 103 ]. In this study, they show that A-allele carriers exhibited better BP control and were less likely to develop uncontrolled hypertension.…”
Section: Literature Reviewmentioning
confidence: 82%
“…In this study, the rs1159744 G>C was associated with the greatest decrease in ambulatory BP responses to HCT and was also associated with significant differences in urinary potassium excretion. A study by Masilela et al, among Nguni South African patients on HCT, reported an association of the WNK1 rs2107614 SNP with uncontrolled hypertension (>140/90 mmHg) [ 103 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In a European Mendelian randomization, modifiable risk factors such as obesity, salt intake, body mass index, alcohol dependence, smoking, coffee consumption, physical activity, sleep duration, and educational factors were found to be causal HTN risk factors [40]. A study of 291 Black South Africans confirmed the presence of SNPs associated with hydrochlorothiazide, some of which were significantly linked to uncontrolled HTN and suggests the need for further investigation of personalized therapy [41]. Furthermore, among self-reported Blacks in Systolic Blood Pressure Intervention Trial (SPRINT), a higher proportion of West African ancestry was associated with a modestly lower risk for CVD events, suggesting that extrinsic and structural societal factors, more than genetic ancestry, may be the major drivers of disparate CVD with HTN in African Americans [42].…”
Section: Regional Aspects Of Hypertension Treatment and Controlmentioning
confidence: 98%
“…To date, no genetic association with EH has been described in South African cohorts [ 18 , 35 , 36 ], though genetic associations in distinct South African ethnic groups have been described with blood pressure traits [ 37 , 38 ] and uncontrolled hypertension [ 16 , 39 , 40 ]. South Africa, with its rich ethnic diversity [ 41 , 42 , 43 ], presents a unique opportunity to unearth ethnic-specific associations, shedding light on the complex interplay between genetics and EH.…”
Section: Introductionmentioning
confidence: 99%